The Influence of the Work Environment on Organizational Commitment Mediated by Employee Job Satisfaction (A Study at the Badung Branch of the Bali Regional Development Bank) - Putri, Ni Luh Maha Cantika; Rahyuda, Agoes Ganesha (Indonesian Journal of Advanced Research, 2025)
Organizational commitment refers to the emotional bond, loyalty, and sense of obligation an employee feels toward their organization. This study investigates the influence of the work setting on organizational dedication, with job satisfaction serving as a mediating element. The research was carried out at the Bali Regional Development Bank (BPD Bali), Badung Branch, involving 45 employees selected through a census approach. Data were obtained through questionnaires and interviews, then analyzed using Path Analysis and the Sobel Test. The findings reveal that the workplace atmosphere and employee satisfaction both have a beneficial and substantial impact on commitment to the organization. Moreover, the work atmosphere positively influences job satisfaction, which then facilitates the connection between the work atmosphere and commitment to the organization.  These results align with social exchange theory,  suggesting that improving the workplace atmosphere and employee satisfaction may lead to greater commitment among staff.